Parametric Study on Parameter Effects in Hybrid Micro Wire Electrical Discharge Turning - Izamshah, R.; Akmal, M.; Kasim, M.S.; Sued, M.K.; Sundi, S.A.; Amran, M. (Journal of Advanced Manufacturing Technology (JAMT), 2018)
In this paper, a comprehensive parametric study on the effects of operating parameters in wire electrical discharge turning (WEDT) process was conducted. Total of eleven operating parameters were considered against the machined surface quality. The research focuses on the micro-turning of Ti6Al4V materials using Taguchi’s L12 orthogonal array at two level experimental designs. Analysis of variance (ANOVA) and signal-to-noise (S/N) ratio were used as statistical tools to evaluate the significances of the parameters. It was found that among the eleven operating parameters, only four parameters dominated and have statistical significant effects on the surface roughness values as discovered by ANOVA. The operating parameters were the rotational spindle speed (28.34%) as the most dominating factor, followed by intensity of pulse (24.18%), wire tension (20.57%) and stabilizer E (11.97%).